Aberrant Presentation of Canalis Sinuosus: A Rare Case Report - Akshay Agarwal; Preeti P Nair; Ganiga Channaiah Shivakumar; Annette Bhambal (Journal of Indian Academy of Oral Medicine and Radiology)
The intraosseous path of the anterior superior alveolar nerve (ASAN) and vessels known as canalis sinuosus (CS) can present as a tortuous channel along the infraorbital region and walls of maxillary sinus. This usually terminates in the anterior maxilla in the palatal region through small accessory foramina. These kinds of aberrant neurovascular structures in the anterior maxilla carry potential risk of iatrogenic injuries and associated complications. This article describes bilateral CS with a rare presentation of large palatal foraminal opening along with anastomosis between left and right CS.